PEMEROLEHAN BAHASA PADA TATARAN FONOLOGI DAN SEMANTIK (STUDI KASUS ADRIAN) - Marcelino Raharjo; Misbah Priagung Nursalim (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2020)
The study discusses language acquisition at the phonological level and the forms of behavior in language acquisition at the semantic level reviewed using the theory of behaviorism. The importance of this research is because the case that that happened to Adrian who had problems in language division due to the isolation carried out on Adrian. This research was conducted to find out: 1) acquisition of Adrian language at the phonological level; 2) The forms of Adrian’s behavior in the language acquisition at the semantic level is terms of the theory of behaviorism. The method used is descriptive qualitative. The approach used is behaviorism which is integrated using the technique of the listening and competent. This study uses the theory of behaviorism by B.F Skinner to review the form of Adrian’s behavior. The result was Adrian’s mastery of vowels, consonants and diphthongs at the phonological level. Stimulating stimulus for language acquisition at the semantic level changed Adrian’s acquisition of language